(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This article is devoted to the main provisions of the methodology of teaching foreign languages in secondary school. These provisions, however, determine only the general direction of the learning process. The methodology of teaching foreign languages deals primarily with the nature of linguistic phenomena, since the teacher of this subject has to consider the systems of two languages, has to compare these two systems and, consequently, reveal to students the nature of many linguistic phenomena.